Prevalence and characteristics of non-syndromic hypodontia among Turkish orthodontic patient population - KARGÜL, BETÜL (MEDKNOW PUBLICATIONS & MEDIA PVT LTD, 2015)
Background: Hypodontia is often used as a collective term for congenital absence of primary or secondary teeth, although specifically it describes the absence of one to six teeth excluding third molars. The prevalence of hypodontia varies from 0.03 to 10.1% in various populations. Materials and Methods: In this retrospective study, we reviewed the records of Turkish orthodontic patients treated between 1994 and 2003. A total of 1236 orthodontic patients (507 girls, 729 boys) were included in this study. The age of the patients ranged from 11 to 20 years. Data were collected and entered into the SPSS 20 program for statistical analysis. The Chi-square test was used to analyze differences in the distribution of hypodontia, sex, and malocclusion type. Results: In the total sample of 1236 patients who were orthodontically treated, hypodontia was found in 82 children, including 45 girls and 37 boys. The prevalence of hypodontia was 7%. Patients with more severe hypodontia showed a tendency to exhibit a class II relationship. The mandibular second premolar were the most commonly missing teeth in 48 girls and 26 boys. Conclusion: Hypodontia may lead to some clinical problems including malocclusions, esthetic and functional complaints, and also psychological problems. All cases should be evaluated by an interdisciplinary approach for appropriate treatment choice. Our data emphasize the importance of detailed and careful radiographic examination. This helps in long-term and effective treatment planning according to a childs individual requirements.
Keywords: Absence of third molar; non-syndromic hypodontia; orthodontic patient